REPRESENTASI TRAUMATIK PEREMPUAN KORBAN PEMERKOSAAN DALAM FILM 27 STEPS OF MAY (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Sry Novita; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Rape is one of the problems of women in social life which is made into a film. The victim of rape must suffer both physical and psychological consequences. Traumatic is one of the psychological impacts which is rarely found in conventional media. Through the film 27 Steps Of May, director Ravi Bharwani presents a visualization of the traumatic experiences of women victims of rape.This type of research is a qualitative research with a constructivist paradigm. This research uses Charles Sanders Peirce's semiotic model which consists of representamen (sign), object, and interpretant as a tool to analyze the traumatic meaning of women victims of rape in 27 Steps Of May.The results of this study are: (1) Traumatic behavior of women victims of rape is represented by a sign or representation in the form of using Close Up, minimal dialogue, and not using bright colors. It is used as a visual support for traumatic impressions. (2) The traumatic behavior of women victims of rape in 27 Steps Of May is represented by the object through the appearance and behavior of May's figure. May's traumatic behavior is supported by pale and dark colored clothes which mean sadness, pain, and boredom. (3) The traumatic of women victims of rape in the film 27 Steps Of May is represented by interpreters through May who are identified as having shock behavior, sleep disturbances (insomnia), introvert, emotional immunity, self harm, flashback, panic attack, nausea and gag. (4) Hanik found traumatic symptoms in the film 27 Steps Of May in the form of flashbacks and emotional immunity. (5) The results of interviews with informants found that the traumatic behavior of rape victims in this film is difficulty interacting with other people, shutting down, flashbacks, self-harm, shock, gloom and cold behavior, and experiencing insomnia. Keywords: Rape, Traumatic, Film, Representation, Semiotic